Caregivers’ Work Satisfaction and Individualised Care in Care Settings for Older People - Suhonen, Riitta; Katajisto, Jouko; Charalambous, Andreas (My University, 2012)
Aim and objectives. To examine the association between caregivers’ work satisfaction and individualised care in different care settings for older people. Background. Work satisfaction in older people care settings has been associated with absenteeism, staff turnover and the quality of care delivered. The management of individuality is an important quality of care issue. Although these two issues are important there is little evidence about the possible association between them. Design. An exploratory and correlational survey design. Methods. Data were collected using three questionnaires, the Individualised Care Instrument the Individualised Care Scale- Nurse and the Index of Work Satisfaction from a sample of professional nursing caregivers (n = 263, response rate 71%) in care settings for older people in one health care area in Finland in 2010. Statistical analysis included descriptive statistics, correlations, analysis of variance and multiple regression analysis. Results. Caregivers support the patient’s individuality through specific activities, perceiving that they maintain individuality in care provision whilst reporting moderate work satisfaction. The ratings of individuality assessments were the lowest in nursing homes followed by long-term care in in-patient wards. There were statistically significant correlations between work satisfaction and specific perceptions in the support of individuality. The sub-scales of the instruments used were: the Support of Individuality in general, Individuality in the Care Provided, Knowing the Person, Staff-to-Resident Communication and Staff-to-Staff Communication. Significant statistical differences in the results were found between staff working in home care, primary health care, in-patient wards and nursing homes. Conclusions. Low job satisfaction can affect the provision of individualised care emphasising the need to promote individualised care at an organisational level as a means of improving work satisfaction. Relevance to clinical practice. Instruments to measure work satisfaction and individualised care can be used to improve care quality.
Keywords: Individuality; Nursing; Older people; Survey; Caregivers